HEMOGRAM OF DOGS WHICH SUFFER COMPLEX DERMATITIS TREATMENT BY MIXTURE OF SOURSOUP, NEEM, AND GOTU KALA LEAVE - Wulandari, Wulandari; Suartha, I Nyoman; Kendran, Anak Agung Sagung; Sudimantini, Luh Made (Buletin Veteriner Udayana, 2021)
Dermatitis complex is a disease of inflammation at the skin caused by two agents or more. Extract of soursop, neem, and gotu kola are known to have an effect that can help cure complex dermatitis. Blood is an important indicator for knowing body health status, so the patient's hemogram needed to know. This research aims to find out the hemogram of dermatitis complex dogs treated by a mix of extract soursop, neem, and gotu kola. This research used three sample dogs that suffer complex dermatitis, which smeared with extract for 15 days. Blood collection was done at 0 day, three days, seven days, and 15 days of treatment. Blood testing was done by the Animal Blood Counter iCell-800Vet machine. The hemogram result indicates fluctuation in hemogram component, preference rise of leukocyte and lymphocyte, and anemia.